KOMODITI PANGAN (PADI, JAGUNG DAN KEDELAI) UNGGULAN DAERAH KOTA DI PROVINSI SUMATERA BARAT - Syahrial Syahrial; Welly Herman (Diponegoro University, 2019)
Food is a necessity for all residents in both rural and urban areas so that food availability must be guaranteed to meet the needs of all residents. Several government programs have been carried out to achieve food self-sufficiency, especially rice, corn and soybeans. This study aims to (1) identify the leading food commodities in the city in West Sumatra Province. (2) analyzing the specialization and localization of superior food commodities in the city in West Sumatra Province. (3) identifying priority food commodities that can be developed in urban areas in West Sumatra Province. This research was conducted in (7) seven urban areas in West Sumatra Province. This study uses secondary data which includes production, price and production value. The results of the analysis showed that (1) only rice commodities became the main commodity in all urban areas, (2) pajale commodities spread in several districts in all urban areas, (3) and only rice commodities became priority commodities in several urban areas. So that the development of food commodities in urban areas in West Sumatra Province can be prioritized on rice commodities to meet the food needs of its population.